Synthesis and characterization of an adipic acid–derived epoxy resin. Issue 16 (20th May 2016) - Maiorana, Anthony; Subramaniam, Bhagyashree; Centore, Robert; Han, Xiaorui; Linhardt, Robert J.; Gross, Richard A.
ABSTRACT: Adipic acid, a highly abundant chemical that can be produced from biomass, was used to prepare an aromatic‐free epoxy resin. Synthesis of the diglycidyl adipate was performed by a one‐step process using epichlorohydrin and by a two‐step process comprising allylation and epoxidation. The viscosity of diglycidyl adipate is 25 mPa·s, which is 99% lower than the diglycidyl ether of bisphenol A (DGEBA). The storage modulus at 25 °C for cured diglycidyl adipate and DGEBA is 2000 and 3200 MPa, respectively. The alpha transition temperature through peak of the loss modulus and the peak of tan( δ ), are 77 °C and 90 °C, respectively. Low‐viscosity epoxy applications are discussed herein. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2625–2631 Abstract : This work details the synthesis and characterization of diglycidyl adipate, a bifunctional epoxy resin derived from adipic acid with comparable properties to an aromatic epoxy resin based on bisphenol A. The results demonstrate that simple aliphatic epoxy resins can yield surprising properties before and after cure when compared to an aromatic resin. This is encouraging for the exploration of new epoxy resin building blocks that have the potential to be sustainably sourced and have lower costs than aromatics.